Potent mutagenicity in the Ames test of 2‐cyano‐4‐nitroaniline and 2, 6‐dicyano‐4‐nitroaniline, components of disperse dyes. (22nd September 2015) - Josephy, P. David; Zahid, Muhammad; Dhanoa, Joban; de Souza, Giovanna Brondino Duarte; Groom, Hilary; Lambie, Meghan
Abstract : Genotoxicity data on commercial azo dyes and their components remain sparse, despite their widespread use. We have tested the mutagenicity of 2‐cyano‐4‐nitroaniline (CNNA) and 2, 6‐dicyano‐4‐nitroaniline (CNCNNA), components of azo dyes such as Disperse Blue 165 and Disperse Red 73, in Ames test strains. Both compounds are extraordinarily potent frameshift mutagens, with much greater activity than structurally similar dihalonitroanilines and halodinitroanilines. Analysis of the responses of strains over‐expressing or deficient in bioactivation enzymes shows that bacterial nitroreductase and acetyl CoA: arylamine N ‐acetyltransferase are important mediators of the mutagenicity of CNNA and CNCNNA. Environ. Mol. Mutagen. 57:10–16, 2016. © 2015 Wiley Periodicals, Inc.